MODERASI BERAGAMA DALAM KONTEKS STUDI SYARIAH: TANTANGAN DAN PEMAHAMAN YANG BERAGAMA - Asnita, Dessy; Ryzka Dwi Kurnia; Asih Pertiwi (TERAJU: Jurnal Syariah dan Hukum, 2024)
This paper discusses the importance of religious moderation in the context of Sharia studies and the associated challenges and understandings of religion. The religious moderation movement has a significant impact on maintaining sustainability, social harmony, and interfaith coexistence in contemporary Muslim society. Despite the diverse views on religious moderation, it is essential to understand that this concept should lead to the preservation of strong faith in Aqidah while practicing tolerance in religious matters. This article also examines various perspectives of scholars and thinkers regarding religious moderation, both in support and doubt. This research employs a qualitative research approach to explore differing viewpoints and understand complex issues within the context of religious moderation. The research findings indicate that moderation is not intended to undermine Aqidah but rather to strengthen it by maintaining tolerance in specific areas such as creed, jurisprudence, ethics, transactions, and economics. A balanced understanding of religious moderation can serve as a strong foundation for creating a peaceful and united Muslim community, in line with Islamic values that emphasize peace, harmony, and interfaith coexistence.